Extraction of Polyphenols from Barley (Hordeum vulgare L.) Grain Using Ultrasound-Assisted Extraction Technology - Wang, X.J.; Qi, J.C.; Wang, X.; Cao, L.P. (Asian Journal of Chemistry, 2012)
The optimized ultrasound-assisted extraction (UAE) were developted for extracting polyphenols from barley grain in this work. The process parameters were optimized using response surface methodology (RSM) to maximizing total polyphenol yield (TPY) and total phenolic acid yield (TPAY). Four parameters were included, viz., ethanol concentration (EC), solvent to material ratio (SMR), extraction time (ET) and extraction temperature (ETP). Results indicated that EC was the most significant factor (p < 0.01) both for TPY and TPAY, while ET insignificant (p > 0.05). The practicable optimal conditions for TPY were: EC, 97 %; SMR, 54 mL/g; ET, 20 min; and ETP, 50 ºC, while for TPAY were: EC, 100 %; SMR, 60 mL/g; ET, 18 min and ETP, 50 ºC. Under the respective optimal conditions, TPY could reach to 25.56 mg of tannic acid equivalent/g barley powder (BP), while TPAY could reach to 19.68 mg of gallic acid equivalent/g BP. The experimental values were significantly agreed with the predicted values calculated from the second-order models both for TPY and TPAY, thus verifying that the methods established were applicable and reliable in practice. The use of sonication can enhance the yield efficiently in barley grain polyphenol extraction.